A study of the historical and linguistic factors that shaped Modern Spanish - Bentley, Emma (Linguistics, 2022)
Based on the perspectives and findings of descriptive linguists and typologists, this thesis presents a largely discursive qualitative analysis of how the morphosyntactic changes in Spanish, since its emergence as a separate code from Latin, are linked to both external and internal systems. The morphosyntactic changes follow the course of the three distinct phases of Spanish: Medieval Spanish, Early Modern Spanish and Modern Spanish. Medieval Spanish (español medieval or romance castellano) was used from the 9th to the start of the 15th century. Early Modern Spanish (español medio or áureo) was used from the 15th to the 17th centuries. Modern Spanish (español moderno) has been used since the 17th century. The external systems are understood as the political, historical, societal, and individual elements at play, whereas the internal system refers to systematic linguistic changes. This perspective of the analysis is concerned with how exposure to other language communities, including those speaking substrate languages of former times, as well as other social contexts including ruling social communities has influenced the changes which emerged in the shape of present-day Spanish. However, the findings in this analysis also show that the reasons for the acceptance of many of the structural changes have been due to their frequent use in the spoken form. The analysis investigates the sociolinguistic context for these morphosyntactic developments, supported by existing research on language contact, historical linguistics, including grammaticalisation and sound change regularity. In doing so, this study considers how the past has influenced the present shape of Spanish and considers which sociolinguistic and contact factors were involved. The main findings are that, however great the exposure of Spanish to other language communities has been, the changes to its morphosyntactic system have been subjected to a number of internal grammatical and sociolinguistic conditions. Grammatical conditions may include its typological profile, grammaticalisation, and phonological changes. Sociolinguistic conditions include the speaker's choice, linguistic adaptation and receptiveness to change. The role the Real Academia Española (RAE) has played since the 18th century in promulgating linguistic uniformity in the grammar, orthography and lexicon of the Spanish language has been pivotal for the standard written form of the language. Whilst bringing about uniformity in the written language, it has still allowed for linguistic variation in the vernacular, both within Spain and beyond its borders. This is in line with its role as the umbrella academy to the Asociación de Academias de la Lengua Española (ASALE). This would suggest that the uniformity in the written language has managed to bolster effective communication amongst the different Spanish speaking nations.